Social media influencer or traditional celebrity? Moderational analysis on the relationship between endorser type and endorsement effectiveness - Chen-Yueh Chen; Yi-Hsiu Lin; Tzu-Yun Yeh; Ya-Lun Chou; Tsu-Lin Yeh (PLoS ONE, 2025)
The effectiveness of an endorsement depends on the endorser. Social media influencers and traditional celebrities are both prized as endorsers by advertisers. Studies comparing the effectiveness of these two endorser types has yielded inconsistent results. The effectiveness of a type of endorser depends on the advertising context. The present study explored the moderating effects of product–endorser fit, popularity, self-congruity, similarity, and likeability on the relationship between endorser type and consumer attitudes toward an endorsement in two different sporting contexts. A multiple-factor, independent sample, pretest–posttest, quasi-experimental design was implemented. In total, 473 participants were enrolled in four experiments. Data were analyzed using two-way analysis of covariance and hierarchical linear regression. The results indicate that product–endorser fit, popularity, self-congruity, and similarity but not likeability moderate the relationship between endorser type and consumer attitudes toward an endorsement. This study contributes to the literature on endorsement marketing and helps marketers more effectively choose an endorser that fits the given marketing context.